PENGARUH MEDIA SOSIAL WHATSAPP TERHADAP KEBUTUHAN AFILIASI KOMUNITAS ORANG MUDA KATOLIK (OMK) GEREJA KATOLIK SANTA MARIA PEKANBARU - Maria Laora Sitinjak; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Communication enables the occurrence of social cooperation, making important agreements, and so forth. In the development of social media, WhatsApp itself is one of the most popular social media in the process of accessing it seems practical and simple compared to other instant social media messaging. Therefore, the use of social media whatsapp can lead to the need for the affiliation of the community of Catholic Youth (OMK) of Santa Maria Pekanbaru. This study uses the theory of Computer Mediated Communication (CMC) with the aim of research is to find out how much influence influence between whatsapp social media on the affiliate needs of the Catholic Youth Community (OMK) of the Catholic Church of Santa Maria Pekanbaru.The method used is quantitative explanation using a saturated sampling technique (census) and a total sample of 100 respondents. The researcher collected data with a questionnaire. To find out how much influence between variables X and Y variables, researchers used simple linear regression analysis. Processing questionnaire test data was carried out using the SPPS program Windows Version 25.Based on the results of simple linear regression, the regression coefficient value obtained in this study is Y = 25.944 + 0.264 X with a significance level of 0.000. The level of significance is smaller than α = 0.05. meaning that there is an influence between whatsapp social media and the affiliate needs of the Catholic Youth Community (OMK) of the Saint Mary Catholic Church in Pekanbaru. The magnitude of the effect that occurs is equal to 12.2% and entered into the category of influence is very weak, the remaining 87.8% is influenced by other variables not included in the study. This percentage shows that each person can vary in using social media owned and depends on how they are used. It turns out that the respondent's affiliate needs are fulfilled not only through whatsapp social media, but also the needs of affiliates can be fulfilled by accessing other social media such as Instagram, Facebook, Line, and so on. With these results, in this study it was found that H0 was rejected and Ha was accepted.Key Word: Media Social, Theory of CMC, The needs of affiliation